Evaluasi Program Manajemen Pembinaan Prestasi Cabang Olahraga Petanque Pengcab Fopi Kabupaten Aceh Tenggara - Afrizal, Afrizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the management of achievement development for the Petanque sport in the FOPI Regional Government of Southeast Aceh Regency. This research uses a qualitative descriptive method. The data sources in this research were athletes, trainers and petanque administrators of the FOPI Regional Government of Southeast Aceh Regency. Data collection techniques were carried out using observation, interviews and documentation. This study found that the Petanque assisted by FOPI Southeast Aceh Regency has adequate facilities and infrastructure to support training. There are administrators who double as coaches, but manage management. The Petanque Club under the guidance of FOPI Southeast Aceh Regency still lacks funds for training needs and taking part in championships. Training schedule, management within the organization, achievement goals, and actual achievement In conclusion, the Petanque assisted by FOPI Southeast Aceh Regency has adequate facilities and infrastructure to support trainings. Keywords: achievement development, petanque, sports